2014
DOI: 10.1007/s10823-014-9237-6
|View full text |Cite
|
Sign up to set email alerts
|

Meaning of Death: an Exploration of Perception of Elderly in a Bangladeshi Village

Abstract: The aim of this qualitative study was to explore the perceptions of meaning of death among the elderly in a Bangladeshi community, and to understand how the meaning of death affects one's overall well-being. Understandings of death were explored through the explanations respondents provided on the journey of the soul during lifetime and the afterlife, concepts of body-soul duality, and perceived "good" and "bad" deaths. The relationship to well-being was expressed in terms of longevity, anxiety/acceptance of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 26 publications
0
28
1
1
Order By: Relevance
“…, Joarder et al . ). With the exception of one urban–rural study (Knight ), all the included studies were classified as being solely rural in focus.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…, Joarder et al . ). With the exception of one urban–rural study (Knight ), all the included studies were classified as being solely rural in focus.…”
Section: Resultsmentioning
confidence: 97%
“…One study focused on the ‘bad death’ (Joarder et al . ). The ‘good death’ referred to the death event, the dying process, the meaning of death and the after‐death concept.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Here the sick bed and the process of dying tend to be confined to the seclusion of the house, while the funeral is public. Joardar has shown that Bangladeshi people define ‘good death’ as that which takes place in the presence of loved ones (Joardar et al., 2014). In contrast to the notion of autonomy in Western culture, the collective or relational self plays a more prominent role in individual life in Bangladesh.…”
Section: Introductionmentioning
confidence: 99%